2020
DOI: 10.3390/vaccines8030456
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Protection of Hepatitis B Vaccination among Different Genotypes

Abstract: Hepatitis B (HB) vaccination is the most effective method for preventing HB virus (HBV) infection. Universal HB vaccination containing recombinant HB surface antigens (HBsAg) is recommended. Our data revealed that human monoclonal HB surface antibody (anti-HBs) from individuals inoculated with genotype C-based HB vaccine induced cross-protection against HBV genotype A infection. An in vitro infection model demonstrated anti-HBs-positive sera from individuals inoculated with genotype A- or C-based HB vaccine ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 154 publications
0
26
0
Order By: Relevance
“… 9 This is because hepatitis B vaccine is highly immunogenic, with 90–100% protection conferred following a completed hepatitis B vaccination schedule among infants, children, and adults. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 This is because hepatitis B vaccine is highly immunogenic, with 90–100% protection conferred following a completed hepatitis B vaccination schedule among infants, children, and adults. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…9 This is because hepatitis B vaccine is highly immunogenic, with 90-100% protection conferred following a completed hepatitis B vaccination schedule among infants, children, and adults. 10,11 Unfortunately, the HBV immunization coverage rate among pregnant women has not previously been determined in a Nigerian population. In addition, there is no policy or enactment of any policy in Nigeria that makes uptake of HBV vaccination unavoidable to all women prior to pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This observation was confirmed as sequences coding for the major antigenic segments of HBsAg from our samples were predicted to locate within or overlap with genetically diverse regions and as the segments were similar to those predicted by Rezaee et al (2016) [ 26 ], We observed that the area of greatest diversity within the surface gene, in both Australian and non-Australian donor HBV isolates, appeared to incorporate the ‘a’ determinant of HBsAg. The ‘a’ determinant in the MHR is an important region of HBsAg, as mutations within this region have been reported to affect HBV surface antigenicity [ 49 ], cross-genotype vaccine protection [ 50 ] and efficacy of serological HBsAg detection assays [ 25 , 51 ]. We found that, generally, surface gene nucleotide diversity was lower in our Australian donor HBV sequences when compared to those from non-Australian donors.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of vaccinated people subsequently infected, mainly with the most divergent genotypes, have been described[ 80 - 82 ]. Although there is a paucity of data regarding cross-genotype preventive effect, greater protection against homologous genotype/sub-type than against heterologous strains of HBV have been reported[ 83 ]. However, empirical data from regions where the most divergent genotypes are prevalent suggests that cross protection is sufficient to prevent infection.…”
Section: Hepatitis B Virusmentioning
confidence: 99%